THE FEATURES OF DETERMINATION OF SEISMIC LOADS ON STEEL SILOS WITH A FLAT BOTTOM ACCORDING TO DBN V.2.6-221:2021 (Collection of scientific works «Modern structures of metal and wood», 2023)
The article is devoted to the peculiarities of determination of seismic loads on steel silos with a flat bottom according to newly introduced DBN B.2.6-221:2021, harmonized with the global  system  of  European  codification  Eurocode.  The  main  focus  is  on  the  general  methods  of specifying seismic action and the principles of schematizing seismic action for analysis silos. The parameters of the acceleration spectra of the horizontal and vertical components of seismic load and their influence on formation of silos reaction in these directions are analyzed. The recommendations are given for accurate evaluations the inertia-stiff characteristics of silos with a flat bottom in height based  on  the  analysis  of  their  design  features  and physical  and  mechanical  characteristics  of  the particulate material.